Ideal, Gelanggang Faktor Dari Gelanggang Noether - Lalu Hasan Ghoffari; Marena Rahayu Gayatri (Universitas Nusa Cendana, 2023)
Abstract algebra is one of the most interesting sciences in mathematics. Many things are learned in abstract algebra. One of them is the Noetherian rings. A Noetherian ring is a ring that is defined based on a finite ideal set of a ring. The method used is a literature review or also called a literature study, namely research conducted by collecting theories and information related to research with the help of references such as books or scientific journals. One of the theorems formed based on the definition of a Noetherian is that if R is a Noetherian ring, then R[x] is also a Noetherian.